Performance Of Cameroon-Based Intra- And Inter-Crosses Dura X Pisifera Oil Palm (Elaeis Guineensis Jacq.) Population - Beyegue Djonko Honore
A total of 13 progenies of oil palm derived from biparental crosses between five dura mother palms from Cameroon (CMR) and two pisifera palms, one from CMR and the other from the Democratic Republic of Congo (DRC/ex-Zaire) were field-tested to assess their performance for bunch yield, morpho-vegetative, physiological and oil quality traits. The study is a contribution to the evaluation of oil palm germplasm collected by the Malaysian Oil Palm Board worldwide. The research objectives fulfilled in this thesis work were to (i) study the variation of genotypes for phenotypic characters; (ii) assess the genotype-by-environment (GE) interactions effects on traits; (iii) estimate genetic parameters for characters; (iv) assess the combining ability of both pisifera parental palms; (v) assess the stability of genotypes for traits; and (vi) analyse phenotypic correlations among characters. The 13 genotypes were planted in a randomized complete block design (RCBD) with 16-palm plots replicated twice at MPOB Research Stations in Kluang (Johore) and Keratong (Pahang). Genotypes were scored for 49 phenotypic characters/traits following the standard procedures applied at MPOB. The analysis of variance (ANOVA) revealed significant differences (P<0.05 and P<0.01) among genotypes for all characters checked except for (P/B). The GE interactions effect was significant for all characters except ABWT, TEP, OY, O/B, F/B, S/F, M/F, P/B, BWT, PCS, f, TDMP, e, and NAR. The two pisifera parents showed a significant difference for all characters except ABWT, TEP, KOY, OY F/B, O/DM, P/B, BWT, LL, LW, HT, C18:2 and CC. The pisifera palm from CMR showed a higher combining ability for FFBY and BNO over that from the DRC but there was no significant difference among both parental palms for OY, KOY and TEP. Broad-sense heritability estimates for the characters studied were low to moderate for the majority of characters but morpho-vegetative scored higher heritabilities as compared to other clusters of characters, suggesting their greater genetic control of the inheritance. The contribution of the residual variance components to the total variance was on average greater than 50% and that for genotypic variance less than 30% for all characters, indicating a high contribution of environmental factors to the variation observed. FFBY was positively correlated with BNO (r=0.73) and ABWT (r=0.26), its two main components. BNO and ABWT were negatively correlated (r=-0.44) indicating an antagonistic effect of both characters on the performance of oil palm progenies. Despite the discrepancy in the scoring for bunch yield characters, progenies deriving from crosses CMR x CMR showed a relatively higher performance compared to those from CMR x DRC for FFBY. Genotype PK 1875 (CMR x CMR) revealed to be the best performer on the individual trial basis as well as for pooled data over locations with an average bunch yield of 159 kg/palm/yr. Genotypes performed consistently across locations for bunch and fruit characters, with low heritability estimates accounted for all characters in general. Genotypes’ scores for OY varied from 27.7 kg/palm/yr (PK 1657) to 30.8 kg/palm/yr (PK 1721), with a grand mean of 28.2 kg/palm/yr. Genotypes PK 1874, PK 1721, PK 1664, PK 1875 scored above 30 kg oil/palm/yr in average, which correspond to 4.3 - 4.5 t/ha/yr. Positive correlations were found between OY and O/B (r=0.63), O/WM (r=0.43), M/F (r=0.40). KOY showed a significant correlation with K/B (r=0.84), S/F (r=0.26) and K/F (r=0.78). OY showed a significant and negative associations with the endocarp-related characters K/F (r=-0.34), S/F (r=-0.31) and K/B (r=-0.23). The opposite trend was observed between KOY and mesocarp-related characters M/F (r=-0.61), O/DM (r=-0.15), O/WM (r=-0.23) and O/B (r=-0.22). This suggests an opposite dynamic of OY and KOY with respect to their specific component characters. The best scorers for TDMP, BDMP and e were PK 1875, PK 1874 and PK 1944 (CMR x CMR). Genotype PK 1875 recorded the highest scores for BDMP (12.53 t/ha/year) BI (0.48), and NAR (10.39 t/ha/yr) respectively. PK 1657 and PK 1676 (CMR x DRC) were the poorest performers in terms of BDMP, TDMP and e. Genotype PK 1957 (CMR x CMR) was the most vigorous with the highest scores for VDMP (15.9 t/ha/yr), TDMP (27.2 t/ha/yr) and e (0.98 g/MJ). All physiological characters were significantly correlated (P<0.01) one another, with the exception of the pair BI and e. TDMP was strongly correlated to BDMP (r=0.77) and VDMP (r=0.83). BI was strongly correlated with BDMP (r=0.70) but negatively correlated with VDMP and TDMP (r=-0.45). The selection for high vegetative vigour would have a detrimental effect on BI. HT showed a significant positive correlation with FP (r=0.38), PCS (r=0.14), LA (r=0.15), LAI (r=0.15), LL (r=0.13) and f (r=0.15). Genotype PK 1792 could be selected for its lowest HT and relatively low FP, but it is a poor yielder with 126.0 kg/palm/yr of FFB compared to PK 1875 the best yield performer (FFBY=159.34 kg/palm/yr). The correlation analysis for oil quality traits revealed strong significant associations between C16:0 and respectively, C18:0 (r=-0.59), C18:1 (r=-0.81), and IV (r=-0.70). The correlation between C16:0 and CC was not significant. On the other hand, C18:1 was negatively correlated to C16:0 (r=-0.81), C18:2 (r=-0.68), and positively correlated to IV (r=0.46). The correlation between C18:1 and CC was not significant. Selection for high C16:0 would indirectly select for low IV whereas, selection for high C18:1 would equate selection for higher IV. Scoring for C16:0 and C18:1 could not be used as indirect selection criteria for CC, as both traits showed a nonsignificant correlation with CC respectively. The significant positive correlation between C18:0 and C18:1 would imply that selecting for high C18:1 will indirectly select for high C18:0 as well. Selecting for higher C18:0 would indirectly mean to select for lower C16:0 (r=-0.59) and higher IV. The study revealed that genotypes tested scored markedly higher CC (964.37 ppm to 1551.3 ppm) as compared to D x P current planting materials (500 - 700 ppm). Stability of genotypes for characters was studied using the grouping methods of Francis and Kannenberg, and the regression method of Finlay and Wilkinson. Genotypes PK 1875, PK 1944 and PK 1721 were high stable for FFBY, whereas PK 1671 and PK 1668 were the most sensitive to variations of growing environmental conditions. Genotype PK 1875, PK 1664 and PK 1792 were the most stable for BI, PK 1875 being also highly stable for TEP.